2021
DOI: 10.1016/j.parkreldis.2021.06.023
|View full text |Cite
|
Sign up to set email alerts
|

A new alpha-synuclein missense variant (Thr72Met) in two Turkish families with Parkinson's disease

Abstract: Introduction: Missense variants and multiplications of the alpha-synuclein gene (SNCA) are established as rare causes of autosomal dominant forms of Parkinson's Disease (PD). Methods: Two families of Turkish origins with PD were studied; the SNCA coding region was analyzed by Sanger sequencing, and by whole exome sequencing (WES) in the index patient of the first and the second family, respectively. Co-segregation studies and haplotype analysis across the SNCA locus were carried out. Functional studies include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…We calculated the ROC AUC for every protein with at least 10 pathogenic and 10 putatively benign missense variants. We also supplemented the CALM1 dataset by adding variants from CALM2 and CALM3 , which have identical amino acid sequences, and identified additional pathogenic SNCA variants in the literature (Fevga et al , 2021; Daida et al , 2022; Kapasi et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We calculated the ROC AUC for every protein with at least 10 pathogenic and 10 putatively benign missense variants. We also supplemented the CALM1 dataset by adding variants from CALM2 and CALM3 , which have identical amino acid sequences, and identified additional pathogenic SNCA variants in the literature (Fevga et al , 2021; Daida et al , 2022; Kapasi et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Pathogenic variants were primarily obtained from the ClinVar database of clinically relevant variants (August 2022 update) (Landrum et al , 2014) (https://www.ncbi.nlm.nih.gov/clinvar/) and also from HGMD (free version) (Stenson et al , 2003) (https://www.hgmd.cf.ac.uk/ac/index.php). Additional pathogenic variants from SNCA were found though a literature search (Fevga et al , 2021; Daida et al , 2022; Kapasi et al , 2020). Any pathogenic variants present in the gnomAD dataset were removed from the gnomAD set.…”
Section: Methodsmentioning
confidence: 99%
“…The subjects in our study and in the Italian family responded well to levodopa, which is similar to A30P cases, of which symptoms are similar to those of sporadic late‐onset PD 47 . These findings suggest that the severity in clinical symptoms of patients with V15A might be intermediate in patients with known SNCA pathogenic mutations, although there is clinical variability in SNCA missense mutations 52 . It is important to study additional cases to clarify the clinical phenotype of V15A.…”
Section: Discussionmentioning
confidence: 97%
“…The point mutation is located in the fourth of seven imperfect KTKEGV repeats, which are thought to support α-synuclein’s interactions with lipids [ 47 ]. Until the recent discoveries of the T72M and E83Q mutations [ 13 , 14 ], E46K was the only α-synuclein mutation known to disrupt one of the KTKEGV repeats, suggesting it may exert differing effects on α-synuclein biology and pathogenesis than other PD-causing mutations. Studies investigating the effect of the E46K mutation on α-synuclein fibrillization kinetics found that the amino acid substitution increases the protein’s propensity to fibrillize compared to WT α-synuclein [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…While MSA and LBD patients can present with overlapping motor deficits, MSA patients are typically diagnosed earlier in life (50-60 years old rather than >70 years old) and experience a more rapid disease progression compared to LBD patients [2][3][4]. However, while there are eleven known familial LBD mutations in the gene encoding α-synuclein, SNCA, no mutations have been identified in MSA patients [5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%